2019
DOI: 10.1186/s13046-019-1479-2
|View full text |Cite
|
Sign up to set email alerts
|

RNA-binding protein KHSRP promotes tumor growth and metastasis in non-small cell lung cancer

Abstract: BackgroundKH-type splicing regulatory protein (KHSRP) plays an important role in cancer invasion, but the relevant mechanism is not well known. In the present study, we investigated the function and potential molecular mechanism of KHSRP in non-small cell lung cancer (NSCLC) metastasis and elucidated its clinical significance.MethodsIsobaric tags for relative and absolute quantitation and the SWATH™ approach were combined with nanoliquid chromatography-tandem mass spectrometry analysis to identify metastasis-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 41 publications
3
42
0
1
Order By: Relevance
“…However, LINC00662 had no regulatory effects on hnRNPC expression. hnRNPC is a survival-related splicing factor in OSCC [18], and served as the tumor facilitator in non-small cell lung cancer [33], ovarian cancer [16]. The hnRNPC protein is one of the Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, LINC00662 had no regulatory effects on hnRNPC expression. hnRNPC is a survival-related splicing factor in OSCC [18], and served as the tumor facilitator in non-small cell lung cancer [33], ovarian cancer [16]. The hnRNPC protein is one of the Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These ndings suggested that ALKBH5-mTOR pathway may be an available therapeutic pathway for cancer treatment. HNRNPC mainly function as an oncogenic role in cancers [38,39]. Previously, studies found that the abnormally expressed HNRNPC was related to the LBX2-AS1 pathway [40] and JAK-STAT1 signaling pathway [39] in several cancers.…”
Section: Discussionmentioning
confidence: 99%
“…HNRNPC mainly function as an oncogenic role in cancers [38,39]. Previously, studies found that the abnormally expressed HNRNPC was related to the LBX2-AS1 pathway [40] and JAK-STAT1 signaling pathway [39] in several cancers. But the association between the HNRNPC expression and cell cycle related pathway, pentose phosphate pathway, and p53 signaling pathway was rstly reported here, thus the regulatory mechanisms required to be elucidated in future.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the researchers also discovered the overexpression of HNRNPC dramatically accelerated the proliferation, migration, and invasion of lung cancer cells. Moreover, the elevated expression of HNRNPC was signi cantly related to advanced tumor stages, metastasis, and shorter survival time [55]. IGF2BP1, a target of miR-491-5p, was reported to be signi cantly increased in the expression of NSCLC cells, and promoted tumor cell proliferation, migration, and invasion [56].…”
Section: Discussionmentioning
confidence: 99%